1998
DOI: 10.1177/088626098013003001
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Sex Offenders With Deviant Fantasies

Abstract: The Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, and contemporary psychological theory have assigned a central role to deviant sexual fantasy in the genesis, maintenance, and treatment of sex offenders, but empirical studies to support that role are few in number. In this article, 201 male admitting sex offenders and controls were compared on the Clarke Sex History Questionnaire Fantasy Scales. Almost all respondents reported having fantasies of adult females, but only one third of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 19 publications
1
23
0
2
Order By: Relevance
“…Numerous researchers have also highlighted the potential importance of fantasy in sexual offences (see Drieschner & Lange, 1999;McMurran, Hodge, & Hollin, 1997;Pithers, 1990;Ward & Siegert, 2002), as well as its potential significance in the etiology of sexual orientation (Storms, 1981). Despite these concerns, contemporary inquiry lacks a fully integrated theoretical framework to conceptualize the complexity of sexually aberrant behavior (Ward, 2000;Ward & Hudson, 1998b), with a number of researchers suggesting that the results of previous investigations addressing the role of sexual fantasy in aberrant sexual activity have a limited scope due to methodological considerations (Baumgartner, Scalora, & Huss, 2002;Langevin, Lang, & Curnoe, 1998;Leitenberg & Henning, 1995).…”
Section: The Content Of Sexual Fantasy In Sexual Offendingmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous researchers have also highlighted the potential importance of fantasy in sexual offences (see Drieschner & Lange, 1999;McMurran, Hodge, & Hollin, 1997;Pithers, 1990;Ward & Siegert, 2002), as well as its potential significance in the etiology of sexual orientation (Storms, 1981). Despite these concerns, contemporary inquiry lacks a fully integrated theoretical framework to conceptualize the complexity of sexually aberrant behavior (Ward, 2000;Ward & Hudson, 1998b), with a number of researchers suggesting that the results of previous investigations addressing the role of sexual fantasy in aberrant sexual activity have a limited scope due to methodological considerations (Baumgartner, Scalora, & Huss, 2002;Langevin, Lang, & Curnoe, 1998;Leitenberg & Henning, 1995).…”
Section: The Content Of Sexual Fantasy In Sexual Offendingmentioning
confidence: 99%
“…This is even more prominent in specific behaviors such as sexual aggression (80%; Burgess, Hartman, Ressler, Douglas, & McCormack, 1986) and serial rape (95%; Burgess, Hazelwood, Rokous, Hartman, & Burgess, 1988). Research conducted by Langevin et al (1998) revealed that most sexual offenders reported having nondeviant sexual fantasies involving physically mature females, and some (33.3%) reported having deviant fantasies involving children, or other deviant sexual activities. Research by Looman (1995) has shown that child molesters (57%) fantasize about children under the age of 12 more than rapists or nonsexual offenders.…”
Section: The Content Of Sexual Fantasy In Sexual Offendingmentioning
confidence: 99%
“…Prior research, however, is problematic; inferential statistics are sometimes missing, fantasies of male children and adults are combined, fantasies of rape are combined with fantasies of pain or subsumed within broader 'deviant' categories, and comparison groups sometimes have a sexual offending history [9,20]. Other studies include only one comparison [10,13,14,21] or no comparison [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, prior research has used long fantasy checklists [e.g. 9,10,17,20], providing insights into the prevalence of fantasies but nothing about their nature. Each checklist item is presented as a separate, discrete fantasy (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Langevin et al (1998), it was found that, although deviant sexual fantasy does occur in admitting sex offenders, the baseline rates of sexual fantasy are relatively low. This is important in view of the evidence that deviant sexual fantasy is relatively common in general samples.…”
Section: The Role Of Fantasy In Sex Offendingmentioning
confidence: 92%